Comparison of polyurethane foam dressing and hydrocolloid dressing in patients with pressure ulcers: A randomized controlled trial protocol - Jin, Yan (Medicine (Baltimore), 2021)
BACKGROUND: We conduct this randomized controlled trial protocol for the comparison of the influence of the hydrocolloid dressing and polyurethane foam dressing in the treatment of pressure ulcers (PUs) patients. METHODS: This study will be implemented from February 2021 to February 2022 at Hangzhou Geriatric Hospital. The experiment was granted through the Research Ethics Committee of Hangzhou Geriatric Hospital (C5259033). Criteria for inclusion: patients older than 18 years of age who have been diagnosed with PU. If the patient suffers from more than a PU, only the ulcer with largest diameter is evaluated. Criteria for exclusion: (1).. hypersensitivity or allergy to the substances in dressings; (2).. patients with diabetic foot or venous ulcers; and (3).. serious disease. The major result is rate of PU healing or ulcer epithelialization tissue. The secondary result is the changes in the area of ulcer in cm and cost-effectiveness. The analysis of all the data are conducted with the software of IBM SPSS Statistics for Windows, version 20 (IBM Corp., Armonk, NY). RESULTS: Table 1 will show the comparison of clinical outcomes between 2 groups. CONCLUSION: This study can develop an evidence-based protocol to identify optimal dressings for patients with PUs. TRIAL REGISTRATION NUMBER: researchregistry6294